Understanding and information needs of cancer patients regarding treatment‐focused genomic testing: A systematic review. Issue 4 (16th February 2020) - Wolyniec, Kamil; Sharp, Jessica; Lazarakis, Smaro; Mileshkin, Linda; Schofield, Penelope
Abstract: Objective: To systematically review literature exploring experiences of cancer patients regarding their understanding of treatment‐focused genomic testing as well as their information needs and related themes. Methods: Six databases were searched for the original studies published in English language that explored patients' understanding of the information related to the genomic testing and its implications for treatment of cancer. The Mixed‐Method Assessement Tool was used to examine the methodological quality of selected articles. Results: There were 14 studies (5 qualitative and 9 quantitative) that met inclusion and exclusion criteria. The majority of studies revealed that a considerable proportion of cancer patients lacked good undertstanding of treatment‐focused genomic testing and wanted to be better informed. Some of the factors associated with poor knowledge about genomic testing were low education, older age, low income, and unemployment. The majority of people with cancer preferred face‐to‐face communication with their oncologists to discuss and ask questions about genomic testing and treatment. Most also wanted to receive simple, easy to understand written information about treatment‐focused genomic testing. Conclusions: Genomic testing and its implications for treatment emerge as an important aspect of health care across different types of cancer. The evidence indicates that cancer patients want to understand and be well informed about treatment‐focused genomic testing in order to be part of decision‐making process. Further studies addressing ways to improve cancer patients' understanding and knowledge of genomic testing are needed.